PENDIDIKAN AGAMA ALTERNATIF: STUDI KASUS SEKOLAH ALAM NURUL ISLAM YOGYAKARTA (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2012)
AbstractIn the current age of information, it is increasingly difficult to find a moral bulwark for students who are unsurprisingly still in the developmental age. Some experts indicate that the last bulwark is in religious education. However, religious education yet still receives criticism, excessively oriented to knowledge that has not been able to substantially change the behavior of students in accordance with the religious education they have learned. In the context of taking the religious education closer to the behavior of students in the society, alternative religious education could be an option of solution. In this regard, this is what Sekolah Alam Nurul Islam (Nurul Islam Natural School) of Yogyakarta provides, which is to integrate religious education into other subjects.Â AbstrakDi era informasi seperti sekarang ini semakin sulit menemukan benteng moral bagi anak didik yang nota bene masih dalam usia perkembangan. Beberapa ahli mensinyalir bahwa benteng terakhir berada pada pendidikan agama. Namun, pendidikan agama toh masih mendapat kritik, yang terlalu berÂorientasi pada pengetahuan sehingga belum banyak bisa mengubah perilaku peserta didik sesuai dengan pendidikan agama yang diperolehnya. Dalam konteks mendekatkan antara pendidikan agama dengan perilaku peserta didik dalam masyarakat maka pendidikan agama alternatif bisa menjadi pilihan sebagai solusi. Dan ini yang dilakukan Sekolah Alam Nurul Islam Yogyakarta yaitu dengan mengintegrasikan pendidikan agama ke dalam mata pelajaran lainnya.
Keywords: Natural schools; alternative education; integration; Sekolah alam; pendidikan alternatif; integrasi.